Efeito agudo do óleo essencial de lavandula angustifolia Mill. nos níveis de craving e ansiedade em usuários de crack - Lima, Laysa Karen Soares de (2019)
The topic of drug abuse has been constantly inserted in public health current discussions, mainly due to the different consequences of chemical addiction in the life of the addict and those around him. Among the most devastating drugs of present time, crack stands out because of its low cost, harmful effects and its high potential to generate dependence. In seeking treatment for drug withdrawal, the chemical dependent undergoes several challenges inherent to the abstinence period, such as craving, which is filled with intense anxiety. Due to the failures in traditional therapies, complementary or alternative methods have emerged as treatment strategies for this group, such as aromatherapy, with the use of essential oils. Thus, this study aimed to analyze the acute effect of Lavandula angustifolia essential oil administered by inhalation as a complementary therapy in the management of craving and anxiety in users of crack in abstinence. The research was developed with individuals admitted to a detoxification unit and to therapeutic communities for treatment of chemical dependents, in Paraíba. The sample consisted of 35 volunteers, divided into six groups, being one experimental, one control and one aromatic control for each context investigated. Psychological and physiological measures were taken to verify the presence and levels of anxiety and craving. The experiment was performed through single and individual sessions and developed in three moments: Basal Moment (I), Inhalation Moment (II), Post-Inhalation Moment (III). The data were statistically analyzed by non-parametric methods and the results elucidated that the individuals had medium levels of anxiety and high craving, which were significantly reduced in the groups that used the essential oil and remained stable in the other groups after the aromatic intervention. The same happened with the physiological parameters. It is concluded that the oil exerts an acute reductive effect on anxiety and craving levels and acts on maintaining the heart and respiratory rate of crack users in abstinence.